Quality of life for the aged with chronic diseases and their social representations (Research, Society and Development, 2020)
The objective of this study was to propose an educational technology in the form of a workshop based on the social representations of the elderly about quality of life and objective data on the SF-36 scale. Methodological research with quanti-qualitative approach, supported as a reference from the social representations, according to Serge Moscovici. It was applied a SF-36 scale, a technical group of discussion and a semi-structured interview with the 30 participants at the Health Care Center for the Elderly and Caregiver, in Niteroi, Rio de Janeiro,  Brazil. It was applied a Microsoft Excel program the quantitative statistical analysis of the data was performed by the program – SPSS (Statistical Package for the Social Sciences), version 22.0 and a the qualitative by the analysis of Bardin content. The scale SF36 displayed chronic diseases more frequent: hypertension with 80% and osseous-articular/muscular problems with 76,7%. Three categories emerged revealing the social representations of the elderly participants: 1ª Quality of life, inter-relational aspects and life style of the elderly himself / herself; 2ª Quality of life, spiritual aspects; 3ª Quality of life, socialpolitics and economical dimensiones. It was concluded that the statements of the elderly expressed their representations regarding quality of life, according to the emerged thematic from the answers of SF- 36 scale and a performed intreview. It was also noticed the importance of social representations of the elderly centered on the family and the need for effective public policies, contributing to geriatric nursing, public health and society, aiming to improve the quality of life the elderly with chronic non-communicable diseases.